2020
DOI: 10.1159/000505202
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis on the Survival of Cancer Patients Treated with a Fermented <b><i>Viscum album</i></b> L. Extract (Iscador): An Update of Findings

Abstract: Purpose: We aimed at updating the evidence found in controlled studies addressing general and event-free survival of cancer patients treated with the fermented mistletoe extract Iscador. Methods: The databases Embase, PubMed, CAMbase, Scopus, AMED and Cochrane were searched for clinical studies on cancer patients treated with Iscador. Quality of studies and risk of bias were evaluated according to the Cochrane guidelines and the Newcastle Ottawa Scale. Outcome data were expressed as hazard ratios (HR) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 31 publications
6
40
0
1
Order By: Relevance
“…In a recent published real-world data study on patients with stage IV NSCLC we already demonstrated that patients receiving combinatorial CTx plus add-on VA had a longer mean OS and that this combinatorial treatment was significantly associated with a reduced risk of death compared to patient’s only receiving CTx [ 21 ]. These results are consistent with other published data on the clinical effects of combinatorial VA therapy in cancer patients [ 22 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…In a recent published real-world data study on patients with stage IV NSCLC we already demonstrated that patients receiving combinatorial CTx plus add-on VA had a longer mean OS and that this combinatorial treatment was significantly associated with a reduced risk of death compared to patient’s only receiving CTx [ 21 ]. These results are consistent with other published data on the clinical effects of combinatorial VA therapy in cancer patients [ 22 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…The survival analyses demonstrated that patients in the V-group showed longer survival than those receiving standard of care (a 5.7 month longer adjusted overall mean survival [20][21][22][23]. The relevant negative association of the male gender with survival was observed in our patients and correlated with other published data [24].…”
Section: Cost-effectivenesssupporting
confidence: 86%
“…For survival analysis including Kaplan-Meier curves and right-censored time-to-event analyses the R-package 34 “survival” was applied, version 2.41-3, published by Terry M. Therneau and Thomas Lumley on April 4, 2017 ( https://CRAN.R-project.org/package=survival ). To draw survival curves the package “survminer” was used, version 0.4.0, by Alboukadel Kassambara, Marcin Kosinski, and Przemyslaw Biecek published on June 7, 2017 ( https://CRAN.R-project.org/package=survminer ).…”
Section: Methodsmentioning
confidence: 99%